Supporting Self-Directed Learning in Science and Technology Beyond the School Years - Rennie, Léonie J. (Teaching and Learning in Science Series, 2019)
While much has been written about science education from pre-K through to postgraduate study, interaction with science and technology does not stop when schooling ends. Moving beyond scholarship on conventional education, this book extends the research and provides an original in-depth look at adult and lifelong learning in science and technology. By identifying the knowledge and skills that individuals need to engage in self-directed learning, the book highlights how educators can best support adult learners beyond the years of formal schooling. Through case studies and empirical analysis, the authors offer a research-based exploration of adults' self-directed learning and provide tools to support adults' learning experiences in a wide range of environments while being inclusive of all educational backgrounds.